Rethinking the Unio Mystica: From McGinn to Ibn ʿArabī - Arjun Nair (Religions)
Research into the unio mystica has revealed what seems to be an area of “real discussion” between scholars of different traditions of mysticism, particularly those of Judaism, Christianity, and Islam. Although this research serves as a promising start to the dialogue among scholars, it has also raised many questions about a “shared moment” that is nevertheless expressed in “irreducibly diverse” and distinct ways in each tradition. What purpose, for instance, can generic cross-cultural categories serve when they mean little or nothing to scholars in each tradition? By contrast, tradition-specific vocabularies are profuse and often difficult to represent in interlinguistic contexts without significant explanation. The challenge of translating mystical texts, imagery, and ideas across cultures and linguistic traditions raises obvious concerns about the misrepresentation and distortion of traditions in an environment of post-colonial critique. Nevertheless, the continued promise of dialogue calls for specialists of these traditions—particularly non-western and non-Christian traditions—to approach, assess, re-formulate, and even challenge the categories of mysticism from within the conceptual and theoretical horizons of the traditions that they research. The present study models such an approach to scholarship in mysticism. It offers a (re)formulation of the unio mystica from within the theoretical frame of the 12th/13th-century Muslim/Sufi mystic, Ibn ʿArabī (d. 638/1240) and early members of his school of thought. By unpacking the primary terms involved in such an account—“God”, the “human being/self”, and “union”—from within the conceptual and theoretical horizons of that tradition, it problematizes the prevailing understanding of the unio mystica constructed from the writings of specialists in Christian mysticism. More importantly, it illustrates the payoff in terms of dialogue (incorporating the critique of existing theories) when each tradition operates confidently from its own milieu, developing its own theoretical resources for mysticism rather than prematurely embracing existing ideas or categories.